Justice in action? : social work and social justice in the 21st century : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Manawatu, Aotearoa/New Zealand - Ross, Amy Kaye (Massey University, 2011)
Most social workers today learn about and adhere to international and national commitments which specify social justice as an integral part of social work ethics and values. This research focuses on how eight Aotearoa/New Zealand recent social work graduates (2000-2010) understand social justice and how they integrate it into their social work practice. The study explores whether barriers exist in implementing social justice into social work practice on both a personal and structural level, and if so, what they are. The study is qualitative, utilising a critical ethnographic methodology and a critical theoretical framework. Data collected through the use of focus groups and in-depth interviews is examined with a thematic analytical approach. Analysis identified seven themes which showed that social justice was primarily understood as being able to work for change on a structural level. The themes also highlighted the existence of a number of barriers to the integration of social justice into practice. These barriers were in two key areas, the workplace and the organisation of social work. All participants were in strong agreement regarding these barriers. These findings strongly support previous literature and research which identify a disjuncture for social workers between the definition and practice of social work in a number of areas, particularly in an environment dominated by neoliberal ideology. The concord between participants in this study and the similarity of the findings to data within earlier research suggests that the social work community is facing an ongoing and serious difficulty in ensuring social work is able to fulfil its ethical commitments and protect its workers as they work for social justice. Based on this research five recommendations are made to develop and support the social work community.
Keywords: Social services; Social work; Social justice; New Zealand; Social workers